MMP‐2 and MMP‐13 affect vasculogenic mimicry formation in large cell lung cancer. Issue 12 (2nd August 2017) - Li, Yanlei; Sun, Baocun; Zhao, Xiulan; Wang, Xudong; Zhang, Danfang; Gu, Qiang; Liu, Tieju
Abstract: Matrix metalloproteinases (MMPs) have critical functions in tumour vasculogenic mimicry (VM). This study explored the mechanisms underlying MMP‐13 and MMP‐2 regulation of tumour VM formation in large cell lung cancer (LCLC). In our study, laminin5 (Ln‐5) fragments cleaved by MMP‐2 promoted tubular structure formation by the LCLC cell lines H460 and H661 in three‐dimensional (3D) cultures. Transient up‐regulation of MMP‐13 or treatment with recombinant MMP‐13 protein abrogated tubular structure formation of H460 cells in 3D culture. Treated cells with Ln‐5 fragments cleaved by MMP‐2 stimulated EGFR and F‐actin expression. Ln‐5 fragments cleaved by MMP‐13 decreased EGFR/F‐actin expression and disrupted VM formation. MMP‐13 expression was negatively correlated with VM, Ln‐5 and EGFR in LCLC tissues and xenograft. In vivo experiments revealed that VM was decreased when the number of endothelium‐dependent vessels (EDVs) increased during xenograft tumour growth, whereas MMP‐13 expression was progressively increased. In conclusion, MMP‐2 promoted and MMP‐13 disrupted VM formation in LCLC by cleaving Ln‐5 to influence EGFR signal activation. MMP‐13 may regulate VM and EDV formation.